A Dichotomy in the 1–24 GHz Parsec-scale Radio Spectra of Radio-quiet Quasars - Sina Chen; Ari Laor; Ehud Behar; Ranieri D. Baldi; Joseph D. Gelfand; Amy E. Kimball (The Astrophysical Journal)
We present the parsec-scale radio spectra of a representative sample of 13 Palomar–Green radio-quiet quasars, based on our new Very Long Baseline Array (VLBA) observations at 8.4 and 23.6 GHz and our earlier VLBA studies at 1.5 and 5.0 GHz. The radio core emission generally exhibits a flat spectrum at 1.5–5.0 GHz, which indicates a compact optically thick synchrotron source on a scale smaller than the broad-line region (BLR) radius R _BLR  ∼ 0.01–0.1 pc. The 8.4–23.6 GHz spectral slope remains flat in four objects indicating the inner radius of the radio source R _in  < 0.1 R _BLR , and becomes steep in four other objects indicating R _in  ∼ 0.5 R _BLR . The flat 8.4–23.6 GHz slope sources may be associated with a continuous ejection starting at the accretion disk corona. The steep 8.4–23.6 GHz slope sources may be produced by an interaction of an active-galactic-nucleus-driven wind with the BLR gas or a low-power jet extending to the BLR scale. Seven of these eight objects, which have a flat or steep 8.4–23.6 GHz slope, reside at the Eddington ratios L / L _Edd  < 0.3, and four of the remaining five objects, where the 8.4–23.6 GHz fluxes are too faint to significantly constrain the slope, reside at L / L _Edd  > 0.3. The 8.4–23.6 GHz radio emission in the high- L / L _Edd objects may be weak due to more extended emission from a radiation-pressure-driven wind. Future submillimeter observations can further constrain the inward radial extent of the radio emission down to the coronal scale.